SUE FOR THE STATE ADMINISTRATION OF JUSTICE IN INDONESIA - Sarjiyati Sarjiyati (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
In the welfare state, the duty of the Government is not limited to the implementation of law, but also it is burdened by the obligation to hold public interest. The Government, in executing the duty, has an active role to interfere in people's lives because it sometimes arises a clash among them. Realizing the government's active role in intervening in public life, the government is preparing for the steps to cope with the emergence of misunderstanding / disputes in the state administration between the government and its citizens by forming the State Administration of Justice (PTUN)). With this justice, it is expected that the officials can carry out their duties properly so as to realize good governance, and able to protect the public interest. However, the State Administration of Justice can be said not tosuccessfully perform their functions, as there are still many obstacles faced by justice seekers in the field of state administration. Some of the obstacles to be faced among others are : in terms of setting it in the legislation, related to the deadline for filing a lawsuit, the disputed object, the subject matter is placed as a defendant. In the case of State Administration of Justice locations, which are still minimal in number, the execution of it is still difficult to be implemented because there is no special executorial institution or institutions in implementing the State Administration of Justice ruling sanctions, lack of awareness of the state administrative officials to obey the State Administration of Justice’s decision, and the absence of more detailed provisions about the sanctions if the decision is not implemented. Keywords : Disputes, State Administration of Justice, Indonesia, obstacles.